2013
DOI: 10.1007/s00404-013-2739-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy risk factors for very premature delivery: what role do hypertension, obesity and diabetes play?

Abstract: Premature birth seems to be correlated to gestational hypertension and associated problems in about ¼ of VLBW infants. Further studies should focus on preventing and treating gestational hypertension to avoid premature delivery and associated neonatal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
5
10
0
Order By: Relevance
“…In our study we took each characteristic that was significantly different in our affected and unaffected groups separately and find only the maternal characteristic gestational hypertension is significantly linked to adverse outcome. Our findings linking gestational hypertension to preterm birth are very similar to those of a recent publication by Spiegler et al [15] reporting on pregnancy risk factors for preterm birth, who found 28% hypertension in the adverse outcome group vs 8% in the control group (we find 28% vs 10%). Thus the connection between hypertension and HG pregnancies may explain, in part, the increased risk of poor fetal outcome.…”
Section: Resultssupporting
confidence: 92%
“…In our study we took each characteristic that was significantly different in our affected and unaffected groups separately and find only the maternal characteristic gestational hypertension is significantly linked to adverse outcome. Our findings linking gestational hypertension to preterm birth are very similar to those of a recent publication by Spiegler et al [15] reporting on pregnancy risk factors for preterm birth, who found 28% hypertension in the adverse outcome group vs 8% in the control group (we find 28% vs 10%). Thus the connection between hypertension and HG pregnancies may explain, in part, the increased risk of poor fetal outcome.…”
Section: Resultssupporting
confidence: 92%
“…In several studies maternal hypertension has been shown to be significantly associated with PTB outcomes [2830]. In the current study, we observed a similar trend in which maternal hypertension was significantly associated with all categories of preterm delivery.…”
Section: Discussionsupporting
confidence: 88%
“…A study looking at the biological determinant of late PTB found that placental ischemia as a result of hypertensive diseases in pregnancy increased the odds of late preterm delivery [31]. Other maternal medical conditions associated with increased risk of preterm delivery included placenta previa, placenta abruption, and preterm premature rupture of membranes, all of which are in concordance with other reported studies in the region and globally [16, 17, 19, 29, 30, 32, 33]. Approximately one in ten women in this cohort was infected with HIV and was in treatment to prevent maternal to child transmission (PMTCT).…”
Section: Discussionsupporting
confidence: 76%
“…Spiegler et al investigated the influence of diabetes on the risk of very premature birth, surprisingly finding no significant connection between these two conditions [24]. The limitation of above study is the identification of neonates with very low birth weight born in the 22nd-36th week of gestation with those delivered prematurely, not taking into account premature newborns presenting birth weight adequate for gestational age.…”
Section: Discussionmentioning
confidence: 98%